UPAYA PENINGKATAN PENGETAHUAN TENTANG MAKANAN JAJANAN DAN PEMERIKSAAN GOLONGAN DARAH PADA MURID SD NEGERI 11 LOLONG BELANTI DI KECAMATAN PADANG UTARA - Yustini Alioes; Husnil Kadri (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Community service on the decision-making process in foreign policy aims to improve awareness of high school students in Padang on the importance of foreign policy. Foreign policy is often identified with complexity and far from public sphere. The community service team expects this activity could help high school students understand the decision making process in foreign policy. The community service is conducted with lecture and role-play method of formulating foreign policy. The approach used in this program is Graham Allison’s concept regarding process of foreign policy- making. This activity is designed in several stages. In the initial stages, the team prepares working plans. The second stage is socialization and the last stage is program implementation. It can be concluded that this community service has increased the student’s understanding in regards to the importance of foreign policy. Result of this activity indicates that students’ knowledge on foreign policy is improving. This is calculated based on several indicators i.e understanding on the role of actors in formulating foreign policy, factors affecting foreign policy and impact on the state’s strategy to pursue its national interest.